MTL‐based implementation of current‐mode CMOS RMS‐to‐DC converters. (10th January 2014) - Shaterian, Mostafa; Twigg, Christopher M.; Azhari, Javad
Summary In this paper, systematic implementation of current‐mode RMS‐to‐DC converters based upon MOS translinear (MTL) principle, utilizing symmetric cascoded MTL cell (SCMC) is proposed. Theory of operation and mathematical analysis of both explicit (direct) and implicit (indirect) techniques for realization of SCMC‐based RMS‐to‐DC converters are discussed. The SCMC includes a folded MTL loop and realizes an MTL equation. MTL principle utilizes the square law characteristics of saturated MOS transistors to realize square‐root domain (SRD) functions. The SCMC is constructed by two connected cascoded current mirrors and has a compact, symmetric, and multi‐purpose structure, with capability of implementing the circuits into the programmable and configurable structures. The proposed RMS‐to‐DC converters utilize the SCMC along with a configurable current mirror array. The required squaring and square‐rooting functions are realized using the SCMC, after proper configuration of the current mirror array. The proposed circuits have been implemented using a reconfigurable architecture fabricated in a 0.5 µm CMOS technology. Copyright © 2014 John Wiley & Sons, Ltd.